(untitled) (Colombia Medica, 2019)
• Introducción: Sandfly are known for having vector species for the tropical disease known as leishmaniasis, endemic to West Boyacá; the municipality of Otanche displays one of the main focus for cutaneous leishmaniasis. • Objetivo: To identify the species of sandfly present in an endemic area of cutaneous leishmaniasis in West Boyacá. • Métodos: The search and collection of sandflies was carried out using CDC gravid traps, over a period of twelve hours (18:00- 06:00). Identification was carried out by revising the genitalia on both male and female samples under a microscope. The distribution took as reference households with a history of people infected with this disease, locating them intra, peri and extra domicile. • Resultados: 361 individuals were recollected (252 females and 109 male), belonging to 9 genres and 16 species. 60% of all recollected phlebotominae consists of Nyssomyia yuilli and Nyssomyia trapidoi. Other species recollected and relevant, due to vector precedent, are Lutzomyia hartmanni, Psychodopygus panamensis, Lutzomyia gomezi and Psychodopygus carrerai. • Conclusión: It was established that, due to its abundance and vector precedent for the country and the area under study, Nyssomyia yuilli and Nyssomyia trapidoi constitute the species of phlebotominae which may be involved in the transmission of cutaneous Leishmaniasis in the region.